GAMBARAN MIOPI PADA ANAK SEKOLAH DASAR DI DAERAH RURAL DAN URBAN (Studi kasus Kecamatan Sumowono Kabupaten Semarang dan Kecamatan Semarang Selatan Kota Semarang) - Isnina Adi Indrarini; Henry Setyawan Santoso; Lintang Dian Saraswati; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Myopia is the primary cause of decreased visual acuity in children. World Health Organization stated myopia as the main priority in controlling world blindness in 2020. The aim of the study is to analyze differences in some risk factors for myopia in students of elementary school in rural and urban areas. The study is an observational study which uses cross sectional approach. Population of the study is students grade IV-VI in Sumowono and Semarang Selatan districts with 100 respondents respectively. Analysis bivariate using chi square. Rural area prevalence of myopia is 16% while urban area prevalence of myopia is 37%. It is suggested that parents should watch the children’s behaviors that may cause the development of myopia.